The MPEG Representation of Digital Media - Chiariglione, Leonardo; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2012)
More and more information, audio and video but also a range of other information type, is generated, processed and used by machines today, even though the end user may be a human. The result over the past 15 years has been a substantial increase in the type of information and change in the way humans generate, classify, store, search, access and consume information. Conversion of information to digital form is a prerequisite for this enhanced machine role, but must be done having in mind requirements such as compactness, fidelity, interpretability etc.  This book provides an overview of the basic technology and mechanisms underpinning the operation of MPEG standards. It is a valuable reference for those making decisions in products and services based on digital media, those with general background, engaged in studies or developments of MPEG-related implementations, and those curious about MPEG and its role in the development of successful, standard technologies. Offers an overview of what’s behind MP3, digital television, online movies and why these innovations changed the world; Provides a comprehensive treatment of all aspects of signal digitization; Presents not only the state-of-the-art, but also what are the drivers of what is coming next and what is developing in key R&D labs; Provides examples of new human sense experiences for all sorts of users and new business opportunities these offer.
An Introduction to MPEG Digital Media -- MPEG Video Compression Basics -- MPEG Video Coding Advances -- MPEG Video Compression Future -- MPEG Image and Video Signature -- Audio Coding—The Beginning -- MPEG Audio Compression Advances -- MPEG Audio Compression Future -- MPEG System Basics -- MPEG Multimedia Scene Representation -- MPEG 3D Graphics Representation -- Reconfigurable Video Coding -- Video and Audio Quality Testing -- Acronyms.
Keywords: Signal processing; Image processing; Speech processing systems; Electronic circuits; Computer-aided engineering; Signal, Image and Speech Processing; Circuits and Systems; Computer-Aided Engineering (CAD, CAE) and Design